Muhammadiyah amid Global Ideological Currents: An Analysis of Responses to Right-Wing, Left-Wing, and Post-Truth Ideologies - Miswanto, Agus; Muthahhari, Alfa Nejatullah; Nugroho, Irham; Solikhah, Norma Dewi (Jurnal Tarbiyatuna, 2025)
The rise of global ideological polarization, marked by the strengthening of right-wing and left-wing ideologies as well as the spread of post-truth narratives, poses significant challenges to religious organizations in maintaining ideological moderation and social cohesion. This study examines Muhammadiyah”™s responses to these global ideological currents and analyzes its position in navigating ideological contestation in the contemporary era. Employing a qualitative approach with a literature-based and thematic analysis, this study draws on Muhammadiyah”™s official documents, organizational decisions, intellectual discourses, and relevant scholarly literature. The findings indicate that Muhammadiyah responds to ideological polarization through a framework of critical centrism, grounded in the principles of Islam Wasathiyah, tajdid (renewal), and the Manhaj Tarjih methodology. This approach enables Muhammadiyah to critically engage with both right-wing exclusivism and left-wing secularism while resisting the epistemic distortions characteristic of the post-truth era. Rather than adopting rigid ideological positions, Muhammadiyah promotes a balanced, rational, and ethical Islamic perspective that emphasizes social justice, democratic values, and religious moderation. The study highlights Muhammadiyah”™s role as a mediating force in Indonesia”™s religious and ideological landscape and underscores its contribution to fostering constructive public discourse amid global ideological turbulence.